2019
DOI: 10.1002/adma.201808279
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient, Stable, and Ductile Ternary Nonfullerene Organic Solar Cells from a Two‐Donor Polymer Blend

Abstract: Organic solar cells (OSCs) are one of the most promising cost-effective options for utilizing solar energy, and while the field of OSCs has progressed rapidly in device performance in the past few years, the stability of non-fullerene OSCs have received less attention. Developing devices with both high performance and long-term stability remains challenging, particularly if the material choice is restricted by roll-to-roll and benign solvent processing requirements and desirable mechanical durability. Building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 56 publications
(150 reference statements)
0
80
0
Order By: Relevance
“…The Random Forest regression model identified the LUMO and HOMO of donor1 as the top two features influencing the V oc . These results indicated that the rational design of donor materials plays an important role in fabricating ternary OSCs . Moreover, the LUMO levels of donor materials were closely correlated with OSC characteristics.…”
Section: Discussionmentioning
confidence: 73%
“…The Random Forest regression model identified the LUMO and HOMO of donor1 as the top two features influencing the V oc . These results indicated that the rational design of donor materials plays an important role in fabricating ternary OSCs . Moreover, the LUMO levels of donor materials were closely correlated with OSC characteristics.…”
Section: Discussionmentioning
confidence: 73%
“…Because of the feasibility of ternary strategy to enhance the photovoltaic performance and device stability, PC 71 BM was added as the third component into the PTQ10:Y6 binary system. Table shows the corresponding photovoltaic parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, finely tunable energy levels have been achieved with organic semiconducting alloys, which are widely applied in ternary OSCs . We envisioned that the alloy strategy may provide a versatile avenue to accurately establish the relationship between the HOMO offset and the exciton dissociation process.…”
Section: Introductionmentioning
confidence: 99%